(x - 2)(x ^ 2 + |x - 1|) - x ^ 2 + 2x = 0 x ^ 3 + x|x - 1|- 2x ^ 2 - 2x| * x - 1| - x ^ 2 + 2x = 0 x ^ 3 + x
x|x - 1|- 3x ^ 2 - 2x| * x - 1| + 2x = 0 x ^ 3 + x
x * (x - 1) - 3x ^ 2 - 2(x - 1) + 2x = 0,
x - 1 >= 0 x ^ 3 + x(- (x - 1)) - 3x ^ 2 - 2x * (- (x - 1)) + 2x = 0
x - 1 < 0 x = 2 x = - 1,
x >= 1 x = 1 х = 1 х = 2 ,
X <1 x = 1 x = 2 x
x = 1 x = 2 Рішення x 1 =1,x 2 =2
x/(x + 5) - (1x + 51)/(5 - x) = 50/(x ^ 2 - 25) x/(x + 5) - (1x + 51)/(5 - x) = 50/(x ^ 2 - 25), x = - 5, x = 5 x/(x + 5) - (x + 51)/(5 - x) = 50/(x ^ 2 - 25) x/(x + 5) - (x + 51)/(5 - x) * 50/(x ^ 2 - 25) = 0 x/(x + 5) * (x + 51)/(- (x - 5)) * 50/((x - 5)(x + 5)) - 0 x/(x + 5) + (x + 51)/(x - 5) - 50/((x - 5)(x + 5)) = 0 (x(x - 5) + (x + 5)(x + 51) - 50)/((x - 5)(x + 5)) = 0 (x ^ 2 - 5x + x ^ 2 + 51x + 5x + 255 - 50)/((x - 5)(x + 5)) = 0 (2x ^ 2 + 41x + 10x + 205)/((x - 5)(x + 5)) = 0 (x(2x + 47) + 5(2x + 47))/((x - 5)(x + 5)) = 0 ((2x + 41)(x + 5))/((x - 5)(x + 5)) = 0 (2x + 41)/(x - 5) = 0 2x + 41 = 0 2x = - 41 x=- 41 2 ,x=-5.x=5 Рішення x = - 41/2 Альтернативна форма 1 1 x = - 20 - x=-20 5
введем замену
тангенс х=а
а³+а²-3а-3=0
а²(а+1)-3(а+1)=0
(а²-3)(а+1)=0
а²=3
а₁=-√3
а₂=√3
а₃=-1
теперь используем замену
tgx=√3 ⇒ x=π/3+πn
tgx=-√3 ⇒ x=2π/3+πn
tgx=-1 ⇒x=3π/4+πn